(3GdCSeGA GdCQHYhfs - (3GdSgQhQOj, CHh fUQ, YeQ Hf eMeO Hf YHO Gddg Hf eMeO Hf YHO Gddg, (B632 (3g`s
(3ChdgG (B:s
(3hgj CQHYhf GSeG YXjeI GdfaY def OGhe YdjgG faY Gddg HHQcJgG hHQcI eDdagG SHMGfc dG Edg EdG CfJ jGQH cd TjA hhGQKg jG Edg GdBdgI GdQajY LdGdg GdGSe GdChd hGdKGfj hGdKGdK hGdQGHY hGdNGeS (B: (3jG Gddg GdeMehO aj cd aYGdgs
(3BNQgG (B:s
(3hUdhGJ Gddg GdHQ GdQMje hGdedGFcI GdebQHjf hGdfHjjf hGdUOjbjf hGdTgOGA hGdUGdMjf eG SHM dc TjA jG QH GdYGdej Ydi CTQa GdNdb SjOfG eMeO NGJe GdfHjjf hSjO GdeQSdjf hQShd QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 62s
(3eYLe GdeDdajf (B2 / 575s
(3cTa GdXfhf (B1 / 90s
(3TPQGJ GdPgH (B5 / 153s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds